Perioperative Management in a Cesarean Section Patient with Rheumatic Heart Disease and Pulmonary Hypertension - Leonardo A. J. Lawalata; Mordekhai L. Laihad; Iddo Posangi; Eka Y. Lantang; Barry I. Kambey (Green Publisher Indonesia, 2026)
Background: Pregnancy complicated by rheumatic heart disease (RHD) and pulmonary hypertension (PH) is a high-risk condition with maternal mortality reaching 20–50%. The physiological burden of pregnancy can precipitate cardiovascular decompensation, making perioperative management of cesarean section extremely challenging. Objective: This case report aims to describe the perioperative challenges and the multidisciplinary anesthetic strategy implemented in a high-risk parturient with RHD and PH, emphasizing the rationale for choosing general anesthesia over regional techniques. Methods: A 25-year-old woman (G3P2A0) at 32–33 weeks gestation presented in labor with signs of fetal distress. She had a history of RHD with moderate-to-severe mitral stenosis, moderate tricuspid regurgitation, PH, and atrial fibrillation with rapid ventricular response. Due to significant coagulopathy (INR 2.3), regional anesthesia was contraindicated. The patient underwent general anesthesia with gradual induction, invasive hemodynamic monitoring (arterial and central venous lines), and lung-protective ventilation for an emergency cesarean section. Findings: The procedure was completed successfully with the delivery of a live infant with good Apgar scores. Intraoperatively, the patient remained hemodynamically stable with support from inotropes and vasopressors. Postoperatively, she was managed in the intensive care unit (ICU) for four days before being transferred to the general ward and discharged without major complications. Implications: This case underscores that in specific high-risk scenarios where regional anesthesia is contraindicated, a carefully conducted general anesthesia with invasive monitoring can be a safe and effective alternative.